2014
DOI: 10.1063/1.4892666
|View full text |Cite
|
Sign up to set email alerts
|

Cell-matrix adhesion characterization using multiple shear stress zones in single stepwise microchannel

Abstract: This paper presents a cell chip capable to characterize cell-matrix adhesion by monitoring cell detachment rate. The proposed cell chip can supply multiple levels of shear stress in single stepwise microchannel. As epithelial-mesenchymal transition (EMT), one of hallmarks of cancer metastasis is closely associated to the interaction with extracelluar matrix (ECM), we took advantage of two lung cancer cell models with different adhesion properties to ECM depending their epithelial or mesenchymal properties, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…The question remains as to how Akt activity was elevated in TD cells after TGFβ stimulation. Previously, we have reported that lung cancer cells become resistant to sheer stress after EMT [ 25 ], which is consistent with previously reported findings [ 26 ]. Based on this observation, we attempted to deduce a gene candidate(s) whose altered expression in TD cells contributes to both increased adhesion (e.g., resistance to sheer stress) and intracellular signaling (e.g., toward GSK3β).…”
Section: Resultssupporting
confidence: 93%
“…The question remains as to how Akt activity was elevated in TD cells after TGFβ stimulation. Previously, we have reported that lung cancer cells become resistant to sheer stress after EMT [ 25 ], which is consistent with previously reported findings [ 26 ]. Based on this observation, we attempted to deduce a gene candidate(s) whose altered expression in TD cells contributes to both increased adhesion (e.g., resistance to sheer stress) and intracellular signaling (e.g., toward GSK3β).…”
Section: Resultssupporting
confidence: 93%
“…In our previous work [48], we demonstrated long-term cell culture and cytotoxicity assay using different PDMS devices. Previously, we also performed 6 h cultivation for sufficient cell adhesion to PDMA surfaces [49]. In this study we verified and lowered the incubation time to 3 h, by which time most of the seeded cells had adhered well on the device.…”
Section: Cell Impedance Analysissupporting
confidence: 55%
“…A vital characteristic of cancer metastasis is induction of EMT, which is associated with interaction with the extracellular matrix (20). In the extracellular matrix, the role of the cellular factors is to communicate with the intracellular matrix and a number of these factors have been reported to be associated with EMT, including IL-6, IL-8, VEGF, TGFβ, SNAIL, MMP, TNFα and TWIST.…”
Section: Emt and Tumorigenesismentioning
confidence: 99%